Linear A libation tables : a semitic connection explored - Eu Min, Niki Cassandra (2020)
The writing system of the Ancient Aegean Minoan Civilization, Linear A, is the predecessor to the already deciphered Linear B script (transcribing Mycenaean Greek) and is one of the five writing systems associated with mainland Greece, Crete, and Cyprus before the introduction of the Greek alphabet. Attempts to decipher the writing system have been unsuccessful for several reasons. Unlike the Linear B language (Mycenaean Greek), Minoan, the language hidden behind Linear A and still undeciphered, bears no apparent similarity to Greek, and any ‘translation’ of Linear A based provisionally on Linear B phonetic values has not produced any tangible result. Additionally, the number of Linear A samples available for examination and translation is limited, especially in comparison to that of Linear B. The research undertaken over the course of this project aimed to expand our understanding of the available samples by looking for recurrences in inscriptions from libation tables, using provisionally Linear B phonetic values. By utilizing these recurrences, an attempt was made to explore a potential association of Minoan with Semitic languages. The results show that there is very little in common between Linear A and the Semitic languages examined, at least in the context of Linear A libation tables.